PENGARUH PENAMBAHAN MOLASE MELALUI AIR MINUM TERHADAP KUALITAS KARKAS BROILER (Gallus dometicus) - Laila Dewi Yunitasari; Alfan Setya Winurdana; Risma Novela Esti (AVES: Jurnal Ilmu Peternakan, 2021)
Molase had been used feed additive to cattle adding nutients feed and water. The research was to know effect of molases on carcass, giblet, and abdomen fat. The experiment used 200 Day Old Chicken (DOC) of broiler strain Cobb, this rearch used analysis of variance method of design with 4 treatments and 5 replication was observed, there was P0 = 0% molase, P1 = 1 % molase, P2 = 2% molase and P3 = 3% molase. The results that showed the molase no real effect (P>0.05) on carcass and giblet, the percentage of carcass producef in the research was 69.75±0.58% to71.05±0.4%, and a giblet of 71.65±2.46% to 75.55±4.01%. However significantly (P<0.05) on abdomen fat, the percentage of abdomen fat research was 1.69±0.033% to 1.86±0.031%. based on the results, it can be concluded that the ration by using addition molase 1% produced the hight percentage of carcass and giblet, while produced the low abdomen fat